(untitled) (Economic and Political Thought, 2019)
The National Party issued generally positive opinions on the national past, invariably stressing the need to establish bonds with the fatherland’s history and the traditions of the Polish nation. Polish culture was a domain within which permanent and imperishable values were observed. The heritage of the past was meant to serve as an impulse to construct the nationstate. The principal objective of this article is to present selected elements of the National Party’s views on the state’s political system in the context of political science. Other objectives include outlining the ideological, conceptual and programme-related image of the National Party, along with the factors determining its ideas, concepts, and views, regarding the state’s political system. Analysis of the previous studies on this subject-matter has revealed that the scientific reflection on Polish nationalism is still incomplete, and calls for extensive verification. The subject matter dealt with in this article has filled in a major research gap. Induction was the underlying research method employed by the author. Among the research techniques used in the study, the analysis of various pieces of evidence and traces of political thought became the most prevalent. Other research methods which proved useful in implementing the research objectives included the systematisation of political concepts and a description based on a status-quo analysis.